How can we improve the quality of cataract services for all? A global scoping review. (12th August 2021) - Yoshizaki, Miho; Ramke, Jacqueline; Zhang, Justine H.; Aghaji, Ada; Furtado, João M.; Burn, Helen; Gichuhi, Stephen; Dean, William H.; Congdon, Nathan; Burton, Matthew J.; Buchan, John
Abstract: Background: Cataract is a leading cause of blindness and vision impairment globally. Cataract surgery is one of the most frequently performed operations worldwide, but good quality services are not universally available. This scoping review aims to summarise the nature and extent of published literature on interventions to improve the quality of services for age‐related cataract globally. Methods: We used the dimensions of quality adopted by WHO— effectiveness, safety, people‐centredness, timeliness, equity, integration and efficiency —to which we added planetary health . On 17 November 2019, we searched MEDLINE, Embase and Global Health for manuscripts published since 1990, without language or geographic restrictions. We included studies that reported quality‐relevant interventions and excluded studies focused on technical aspects of surgery or that only involved children (younger than 18 years). Screening of titles/abstracts, full‐text review and data extraction were performed by two reviewers independently. Studies were grouped thematically and results synthesised narratively. Results: Most of the 143 included studies were undertaken in high‐income countries ( n  = 93, 65%); 29 intervention groups were identified, most commonly preoperative education ( n  = 17, 12%) and pain/anxiety management ( n  = 16, 11%). Efficiency was the quality element most often assessed ( n  = 58, 41%) followed by people‐centredness ( n  = 40, 28%), while integration ( n  = 4) and timeliness ( n  = 3) were infrequently reported, and no study reported outcomes related to planetary health . Conclusion: Evidence on interventions to improve quality of cataract services shows unequal regional distribution. There is an urgent need for more evidence relevant to low‐ and middle‐income countries as well as across all quality elements, including planetary health.